Corrosion behavior of surface nanostructured IN718 superalloy at 650°C - Kumar S.; Chattopadhyay K.; Alam Z.; Singh V.; Satyanarayana D.V.V.; Kumar V. (My University, 2025)
In the present study, the process of ultrasonic shot peening (USP) was adopted for developing nanostructures with a grain size of 62 ± 10 nm on the surface of the alloy IN718. The effect of nanostructures was investigated on high-temperature corrosion behavior under cyclic exposure at 650°C for 100 h in different salty environments (weight percent): 100NaCl (T1), 75Na2SO4 + 25NaCl (T2), and 90Na2SO4 + 5NaCl + 5V2O5 (T3). A near parabolic rate law was observed in both non-treated and treated conditions; however, the parabolic rate constant (kp) was reduced for the USP-treated specimens coated with Salt T1 and Salt Mixtures T2 and T3 by nearly 41 %, 52 %, and 50 %, respectively, with respect to the non-treated specimens. Several oxides and spinels such as TiO2, Fe2O3, Fe3O4, Cr2O3, FeVO4, NbO2, NiFe2O4, NiCr2O4, NiVO3, FeNbO4, FeCr2O4, Na2Cr2O7, and Cr2(MoO4)3 and sulfides NiS and FeS and chlorides CrCl3 and NiCl2 were observed in both treated as well as non-treated samples. Copyright © 2021 by ASTM International,